Psikoedukasi Penggunaan Gadget untuk Meningkatkan Self Control pada Anak SDN 08 Tanjung Lago - Desy Arisandy; Rizki Dian Meira Pirdasyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
This community service activity aimed to provide education on gadget use and self-control among students of SDN 08 Tanjung Lago. The method employed was a psychoeducational program on healthy gadget use, which was designed in a structured, interactive, and child-friendly manner.The results of the community service activity showed that the majority of students understood the dangers of excessive gadget use and the importance of managing their time. In addition, students were able to identify concrete strategies to improve self-control, such as limiting the duration of gadget use and prioritizing learning responsibilities before engaging in leisure activities.